Interaction between the incidence of Prodiplosis longifila Gagné (Diptera: Cecidomyiidae) and management practices in tomato crops in Manabí, Ecuador - Bolívar , Gonzalo; Cañarte , Ernesto; Duicela , Luis; Navarrete, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The insect pest Prodiplosis longifila Gagné (Diptera: Cecidomyiidae), causes severe losses to the tomato crop in Ecuador, in the provinces of Manabí, Pichincha, Carchi, Cotopaxi, Azuay, and Chimborazo, where the main producing areas of this solanaceous crop in the country are located. The objective of this research was to study the interaction of the incidence of this pest with tomato crop management practices. The evaluations were carried out in twenty-five production units in different cantons of Manabí: in Bolívar (two), Portoviejo (eight), Rocafuerte (five), Santa Ana (one), Sucre (three) and Tosagua (six). Each unit had an area of 2500 m2, where 25 plants were randomly marked and the number of healthy, infested and damaged shoots was recorded, as well as the number of healthy and damaged fruits. In addition, a survey was applied to growers to determine the management practices carried out during the crop cycle. Descriptive analysis, significance tests, hierarchical clustering and chi-square tests were carried out. It was determined that in the cantons of Portoviejo, Tosagua and Rocafuerte, infestations did not exceed 13 % and a severity of up to 15 %, reaching 25 % of damaged fruit in Tosagua. The agronomic practices applied were trellising, drip and gravity irrigation, collection of infested fruit and chemical insecticides. There was an interaction with P. longifila between infested fruit collection and trellising, which influenced its infestation and severity, respectively. These incidences were significantly high at harvest, where highly toxic insecticide applications were substantially increased indiscriminately.